RETRACTED: Methods of automated detection of travel points when training a collaborative robot - Evstifeeva N.A.; Gurdiumov S.A.; Kleimenov A.A.; Gerasimova A.A. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001